Validation and reliability of the scale Self-efficacy and their child's level of asthma control - Ana Lúcia Araújo Gomes; Emanuella Silva Joventino; Kamila Ferreira Lima; Regina Cláudia Melo Dodt; Paulo César de Almeida; Lorena Barbosa Ximenes
ABSTRACT Objective: To evaluate the psychometric properties in terms of validity and reliability of the scale Self-efficacy and their child's level of asthma control: Brazilian version. Method: Methodological study in which 216 parents/guardians of children with asthma participated. A construct validation (factor analysis and test of hypothesis by comparison of contrasted groups) and an analysis of reliability in terms of homogeneity (Cronbach's alpha) and stability (test-retest) were carried out. Results: Exploratory factor analysis proved suitable for the Brazilian version of the scale (Kaiser-Meyer-Olkim index of 0.879 and Bartlett's sphericity with p < 0.001). The correlation matrix in factor analysis suggested the removal of item 7 from the scale. Cronbach's alpha of the final scale, with 16 items, was 0.92. Conclusion: The Brazilian version of Self-efficacy and their child's level of asthma control presented psychometric properties that confirmed its validity and reliability.